The relationship between subjective oral frailty and adverse health outcomes or medical and dental expenditures in the latter‐stage older adult: A 6‐year longitudinal study. Issue 2 (5th February 2023) - Doi, Tokiko; Fukui, Makoto; Yoshioka, Masami; Okamoto, Yoshifumi; Shimomura, Manabu; Matsumoto, Kimi; Matsuyama, Miwa; Hinode, Daisuke
Abstract: Objectives: The study aimed to investigate the relationship between subjective oral frailty and adverse health outcomes or medical and dental expenditures in the latter‐stage older adult through a 6‐year longitudinal study. Methods: The participants enrolled in the cross‐sectional study were 3564 Tokushima City residents aged 75, 80, 85, and 90 years old who received oral health examinations and who responded to a questionnaire on oral conditions and health behavior at baseline. The data for the occurrence of disability or mortality, and the monthly medical expenditures, dental expenditures, and total medical expenditure of each participant were obtained from the National Health Insurance Database. Results: The total medical expenditure showed significant differences in participants who had difficulties in eating tough foods, difficulties in swallowing tea or soup, and dry mouth when compared to that of healthy participants, in addition to the current medical treatment against the general disease. The 6‐year longitudinal study revealed that participants with subjective oral frailty symptoms, including difficulties in eating tough foods and difficulties in swallowing tea or soup at baseline, had significantly higher medical, dental, and total expenditures among 538 participants without certified nursing care. In addition, those with subjective oral frailty or with less than 19 teeth present were shown to have a higher possibility for the occurrence of disability or mortality by the cox proportional hazard analysis. Furthermore, it was found that medical and total expenditures in older adults with adverse health outcomes were higher than that of healthy participants. Conclusion: These results suggest that subjective oral frailty in the latter‐stage older adult is related to subsequent adverse health outcomes and an increase in medical and dental expenditures.